2021
DOI: 10.1159/000520314
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Recovery at 1 Min after Exercise Is a Marker of Disease Severity and Prognosis in Chronic Thromboembolic Pulmonary Hypertension

Abstract: <b><i>Background:</i></b> Attenuated heart rate recovery at 1 min (HRR1) was demonstrated to correlate with poor prognosis in patients with pulmonary arterial hypertension, whereas its role in patients with chronic thromboembolic pulmonary hypertension (CTEPH) remains unclear. <b><i>Objectives:</i></b> The aim of this study was to investigate the correlations between HRR1 and functional status, echocardiography, hemodynamics, and prognosis of CTEPH. <b><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Better levels of aerobic fitness act beneficially on the autonomic control of post-exercise HR, preserving the vagal reentry velocity in healthy middle-aged adults [ 10 ]. Thus, there is scientific evidence to accept the association between HRR and prognosis of cardiovascular disease, which supports the recommendation of recording HRR for risk assessment in clinical practice, as a routine [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 75%
“…Better levels of aerobic fitness act beneficially on the autonomic control of post-exercise HR, preserving the vagal reentry velocity in healthy middle-aged adults [ 10 ]. Thus, there is scientific evidence to accept the association between HRR and prognosis of cardiovascular disease, which supports the recommendation of recording HRR for risk assessment in clinical practice, as a routine [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 75%
“…Additionally, Inagaki et al also reported that HRR1 was correlated with hemodynamics in CTEPH (group IV pulmonary hypertension) (18). Recently, we reported that HRR1 could independently predict prognosis in patients with CTEPH (19). However, to the best of our knowledge, no one has systematically studied the interaction between BPA and cardiac autonomic function.…”
Section: Introductionmentioning
confidence: 93%
“…Slow HRR has been defined as a reduction in HR 1 minute after the end of exercise from HR at peak exercise (HR peak ) of less than 12 or 14 bpm ( Cole et al, 1999 ). There is evidence suggesting that slow HRR is a prognostic marker in different diseases, such as coronary artery disease, heart failure, and chronic thromboembolic pulmonary hypertension, as well as in individuals with chronic obstructive pulmonary disease (COPD) ( Morshedi-Meibodi et al, 2002 ; Seshadri et al, 2004 ; Lacasse et al, 2005 ; Nanas et al, 2006 ; Lachman et al, 2018 ; Jin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%